Containment Integrity and Sealing Assessment for HTR-PM600 Fresh Fuel Transport Package Under Impact Loading - Hao, Yuchen; Li, Yue; Lin, Musen; Wu, Bin; Ma, Tao; Wang, Haitao; Liu, Bing; Wang, Jinhua (Frontiers in Energy Research, 2022)
Reliable transportation of fuel elements is vital for High Temperature Reactor (HTR) power plant. Therefore, the safety performance of containment boundary in HTR-PM600 fresh fuel transport package under impact loading should be assessed. Specifically, factors such as the structural integrity, bolt safety, and sealing performance of the flange are considered. However, it is not convenient to assess the sealing performance using the helium leakage test without a prototypical experiment. Therefore, to accurately assess the safety performance in the design stage, we propose a detection technique combing with the finite element method to measure the leak channel in the flange for HTR-PM600 transport package. The results show that the boundary containment has no failure, and there is no complete leak channel in the flange of HTR-PM600 package. Hence, this package has a great safety performance under impact loading. This work also provides references for design of fresh fuel transport packages in pebble-bed reactors.